Shaping Children’s Self-Concept Through Storytelling: An Analysis of Interpersonal Communication Interactions at Bunga Tanjong Kindergarten, Tanjung Morawa Subdistrict, Deli Serdang Regency - Novliady, Ferry; Emilia Ramadhani; Safrin; Adlina, Hafiza (Komunika, 2025)
This article aims to explain how storytelling can shape the self-concept of early childhood through interpersonal interactions between teachers and students as well as between parents and children. This study is part of a community service activity conducted at TK Bunga Tanjong, Tanjung Morawa District, Deli Serdang Regency. The analysis uses the Interpersonal Communication Theory (Devito, 2019) to explore the communication dynamics that occur during storytelling activities. The results show that storytelling serves as an effective medium to enhance children's self-confidence, foster two-way communication, and build emotional bonds between teachers and students, and between parents and children. This activity not only improves children's language skills but also gradually strengthens their self-image, self-esteem, and ideal-self.